(untitled) (MMIT Proceedings, 2026)
The article addresses the issue of integrating ESP (English for Specific Purposes) into the teaching of IT disciplines in a technical university as a factor in forming the professional communicative competence of students. The relevance of the study is due to increasing requirements for the linguistic and professional training of future IT specialists in the context of digitalization and globalization of professional activities. The paper analyzes the theoretical foundations of ESP, as well as foreign and domestic studies focused on professional-oriented foreign language teaching in technical education. During the research, a model for integrating ESP into IT discipline teaching was developed and tested, based on an interdisciplinary approach, the use of authentic professional materials, and project-oriented teaching methods. The empirical part of the study was implemented in the form of a pedagogical experiment involving students from IT majors at a technical university. Questionnaires, testing, pedagogical observation, and comparative analysis of results between control and experimental groups were used for data collection and analysis. The research results indicate a positive trend in the formation of students’ professional communicative competence under conditions of integrated learning. It was established that the integration of ESP and IT disciplines promotes the development of a professional terminological base, oral and written professional communication skills, as well as the ability to use a foreign language when solving applied IT tasks. The findings confirm the pedagogical feasibility and effectiveness of an integrated approach and can be utilized in the practice of teaching foreign languages in technical universities.